Why some do but too many don't? Barriers and enablers to physical activity in regional Tasmania - an exploratory, mixed-methods study - Sisitha Jayasinghe; Robert Soward; Timothy P. Holloway; Kira A. E. Patterson; Kiran D. K. Ahuja; Roger Hughes; Nuala M. Byrne; Andrew P. Hills (BMC, 2022)
Abstract Background The interconnectedness of physical inactivity and sedentarism, obesity, non-communicable disease (NCD) prevalence, and socio-economic costs, are well known. There is also strong research evidence regarding the mutuality between well-being outcomes and the neighbourhood environment. However, much of this evidence relates to urban contexts and there is a paucity of evidence in relation to regional communities. A better understanding of available physical activity (PA) infrastructure, its usage, and community perceptions regarding neighbourhood surroundings, could be very important in determining requirements for health improvement in regional communities. The aims of this research were to 1. Explore and evaluate the public's perception of the PA environment; and 2. Evaluate the quantity, variety, and quality of existing PA infrastructure in regional Northwest (NW) Tasmania. Methods A mixed methods approach guided data collection, analysis, and presentation. Quality of PA infrastructure was assessed using the Physical Activity Resource Assessment (PARA) instrument and public perception about PA environment was evaluated using the International Physical Activity Questionnaire - Environmental (IPAQ-E) module. Quantitative data were analysed using descriptive summative methods and a team-based researcher triangulation approach was utilised for qualitative data. Results Overall, a wide array of high-quality PA infrastructure (with minimal incivilities such as auditory annoyance, litter, graffiti, dog refuse, and vandalism etc.) was available. Survey respondents rated neighbourhoods positively. The overall quality of PA infrastructure, rated on a scale from 0 to 3, was assessed as high (all rated between 2 to 3) with minimal incivilities (rated between 0 and 1.5). Of note, survey respondents confirmed the availability of numerous free-to-access recreational tracks and natural amenities across the 3 local government areas (LGAs) studied. Importantly, most respondents reported minimal disruption to their routine PA practices due to the COVID-19 pandemic. Conclusion This exploratory research confirmed the availability of a wide range of high-quality PA infrastructure across all three LGAs and there was an overwhelming public appreciation of this infrastructure. The challenge remains to implement place-based PA interventions that address extant barriers and further increase public awareness and utilisation of high-quality PA infrastructure.